PERLINDUNGAN HUKUM TERHADAP LENDER FINTECH PEER TO PEER LENDING AKIBAT PANDEMI COVID-19 ( PERATURAN OTORITAS JASA KEUANGAN NOMOR 58 /POJK.05/2020 ) - Diana Melati Pakpahan (2021)
Coronavirus Disease (COVID-19) has spread throughout the world including Indonesia. The Indonesian government implements a work from home (WFH) policy. This policy causes many borrowers in the p2p lending financial technology industry to be unable to pay off their credit due to loss of income. This default made by the borrower is very detrimental to the lender. OJK responded to this problem by issuing POJK Number 58 /POJK.05/2020 concerning the Countercyclical Policy on the Impact of the Spread of Coronavirus Disease 2019 for Non-Bank Financial Services Institutions. The problem in this research is how the impact of the spread of the Covid-19 pandemic on Fintech P2P Lending Lenders and how the legal protection of Fintech P2P Lending due to the Covid-19 pandemic based on OJK Regulation Number 58 / POJK.05 / 2020 This issue will be discussed with juridical research methods. empiric, using secondary data, which consists of primary legal materials, namely OJK regulations on Countercyclical Policy and related literature, analyzed descriptively analytically. The results of the study concluded that P2P Lending Fintech Lenders were affected by the spread of Covid-19, so that with the OJK Regulation Number 58 / POJK.05 / 2020 which grants restructuring permits for Fintech companies and regulates the principles of legal protection for lenders in a preventive manner, it is expected to be able to overcome the losses incurred. experienced by lenders during the Covid-19 pandemic. Keywords: legal protection, lenders, fintech peer to peer lending, covid − 19